Role of employee loneliness, job uncertainty and psychological distress in employee-based brand equity: Mediating role of employee exhaustion - Hao Chen; Jingya Li; Juan Li; Jiaying Bao (Frontiers Media S.A., 2022)
Employee-based brand equity plays a crucial role in building organizations' brand equity, and organizations strive to maintain it because of its stimulating effect on competitive achievement. Based on psychological contract and stress theory, this study developed a model that points out the antecedents which can play an adverse role in the EBBE building process. This study explores the role of employee loneliness, job uncertainty, and psychological distress on employee-based brand equity. This study also explores the mediating role of emotional exhaustion in these relationships. For the empirical analyses of the model, this study gathered data based on a 459 sample size under a time-lag approach from the employees of clothing brands in China. This study analyzed the data through partial least square structural equation modeling (PLS-SEM). For this purpose, SmartPLS software was used. The outcomes revealed that employee loneliness has no direct relationship with employee-based brand equity; however, job uncertainty and psychological distress negatively influence employee-based brand equity, such as job uncertainty and psychological distress reduce employee-brand-based equity. Moreover, emotional exhaustion mediates the relationship between employee loneliness and employee-based brand equity and job uncertainty and employee-based brand equity; however, emotional exhaustion does not mediate the relationship between psychological distress and employee-based brand equity. Finally, practical implications, limitations, and future directions are discussed in this study.